Curbing the security council’s powers: thinking the unthinkable? - Qanet, Ghulam Mohammad; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Masum, Ahmad; Nafees, Seeni Mohamed (2021)
Background: The expending role of the United Nations Security Council not only as a global executive organ but also as a quasi-legislative and quasi-judicial body has led many commentators to pose various questions pertinent to its future direction. In view of that, many countries including even high-ranking UN officials as well as numerous commentators are calling for its reform. Objective: Accordingly, this paper aims to examine how the Security Council’s powers have been evolving especially after the Cold War and the challenges its faces along with the expansion of powers. Methodology: This paper employs the qualitative research method in order to achieve its objective. Results and conclusion: It is opposed that there is a need to form an international committee at the UN level to look for the possible avenue to make it more efficient in ensuring international peace and security with impartiality and lack of prejudices among the global powers.